(untitled) (Universal International Scientific Journal, 2026)
This article provides a scientific analysis of the role and methodological foundations of STEAM (science, technology, engineering, art, and mathematics) education in developing creativity and innovative thinking in students at pedagogical universities. According to the study’s findings, students studying with a STEAM approach achieve higher results in creative thinking, critical analysis, teamwork, and practical application of knowledge compared to students studying traditionally. The article presents recommendations and promising proposals for implementing a STEAM approach in the education system of Uzbekistan.